PENINGKATAN HASIL BELAJAR SISTEM KONTROL ELEKTROMEKANIK MELALUI MODEL PEMBELAJARAN PBL SISWA KELAS XI TEKNIK OTOMASI INDUSTRI - Saada, Christofel Jeiver (VOCATIONAL: Jurnal Inovasi Pendidikan Kejuruan, 2025)
This study aims to enhance students’ engagement and learning outcomes through the implementation of the Problem Based Learning (PBL) model in classroom instruction. The research employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of four stages: planning, implementation, observation, and reflection. Data were collected using several instruments, including student activity observation sheets, interviews, end-of-cycle test results, field notes, and documentation of learning activities. The findings revealed a significant improvement in both student participation and academic achievement after the application of the PBL model. In Cycle I, the average level of student learning activity reached 55.2%, with a mean score of 46.9. After the refinement of instructional strategies in Cycle II, student activity increased to 82%, while the average test score improved to 71.04. During the first cycle, some students still scored below the Minimum Mastery Criterion (MMC) of 65; however, in the second cycle, all students achieved mastery, with the lowest score being 67. These results demonstrate that the Problem Based Learning approach effectively fosters a more interactive and reflective learning environment, encourages critical thinking, and promotes active student participation. The increase in engagement was directly correlated with higher learning outcomes, indicating the success of PBL in improving both cognitive and behavioral aspects of learning. Therefore, the PBL model can be considered an effective instructional strategy for enhancing learning quality, particularly in Industrial Automation Engineering courses such as Electromechanical Control Systems. ABSTRAKPenelitian ini bertujuan untuk meningkatkan keterlibatan dan hasil belajar siswa melalui penerapan model Problem Based Learning (PBL) pada kegiatan pembelajaran di kelas. Metode yang digunakan adalah Penelitian Tindakan Kelas (PTK) yang dilaksanakan dalam dua siklus, dengan setiap siklus mencakup tahap perencanaan, pelaksanaan tindakan, observasi, dan refleksi. Data dikumpulkan melalui lembar observasi aktivitas siswa, wawancara, hasil tes akhir, catatan lapangan, serta dokumentasi kegiatan belajar. Hasil penelitian memperlihatkan adanya peningkatan yang nyata pada aspek aktivitas dan hasil belajar setelah penerapan model PBL. Pada siklus I, tingkat aktivitas belajar siswa mencapai 55,2% dengan rata-rata nilai hasil belajar sebesar 46,9. Setelah dilakukan perbaikan pada siklus II, tingkat aktivitas meningkat menjadi 82%, sedangkan nilai rata-rata hasil belajar naik menjadi 71,04. Jika pada siklus pertama masih terdapat siswa yang memperoleh nilai di bawah KKM (65), maka pada siklus kedua seluruh siswa telah mencapai ketuntasan dengan nilai terendah 67. Temuan ini menegaskan bahwa penerapan model Problem Based Learning mampu menciptakan suasana belajar yang lebih interaktif, menumbuhkan kemampuan berpikir kritis, serta meningkatkan partisipasi aktif siswa selama pembelajaran berlangsung. Dengan meningkatnya keterlibatan siswa, capaian hasil belajar pun mengalami peningkatan yang signifikan. Oleh karena itu, model PBL dapat dianggap efektif dalam mengoptimalkan proses belajar khususnya pada pembelajaran Teknik Otomasi Industri di mata pelajaran Sistem Kontrol Elektromekanik.